2011
DOI: 10.1002/ffj.2057
|View full text |Cite
|
Sign up to set email alerts
|

Is the pig a good umami sensing model for humans? A comparative taste receptor study

Abstract: The diversity of taste perception across species reflects a dietary adaptation to different ecological niches. Laboratory rodents have been widely used as models for human nutritional studies including the understanding of peripheral chemosensing. Nevertheless the diet type as well as the anatomical and functional features of bigger mammals such as the pig may merit further consideration as models for humans. Recently, the porcine umami taste receptor pTas1r1/ pTas1r3 and porcine mGluR4 gene sequences have bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 24 publications
(36 reference statements)
1
35
0
Order By: Relevance
“…Owing to the species-specificity, T1R1/T1R3 in different animals can sense different AAs. Murine T1R1/T1R3 can sense up to 18 AAs [83]; human T1R1/T1R3 can sense only glutmate and aspartate [89]; while swine T1R1/T1R3 can sense at most 6 AAs, including glutmate, aspartate, alanine, glutamine, serine and threonine [90]. …”
Section: Amino Acid Signaling To Mtorc1 Initiates At the Cell Membmentioning
confidence: 99%
“…Owing to the species-specificity, T1R1/T1R3 in different animals can sense different AAs. Murine T1R1/T1R3 can sense up to 18 AAs [83]; human T1R1/T1R3 can sense only glutmate and aspartate [89]; while swine T1R1/T1R3 can sense at most 6 AAs, including glutmate, aspartate, alanine, glutamine, serine and threonine [90]. …”
Section: Amino Acid Signaling To Mtorc1 Initiates At the Cell Membmentioning
confidence: 99%
“…However, the differences between rodents and humans in dietary habits, digestive strategies including coprophagy, nutrient requirements and nutrientnutrient interactions suggest the pig may be a closer match than rodents for studying physiological functions relating to these research areas (1)(2)(3)(4) . However, the differences between rodents and humans in dietary habits, digestive strategies including coprophagy, nutrient requirements and nutrientnutrient interactions suggest the pig may be a closer match than rodents for studying physiological functions relating to these research areas (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…Sense of taste The gustatory system of pigs is also well developed Roura et al 2011;Roura et al 2016). Similar to their extraordinary sense of smell, their sense of taste is thought to be the most developed of all mammals, including humans, due to high numbers of taste buds (Bradley 1971;Chamorro et al 1993).…”
Section: Physiological Senses Driving Motivationmentioning
confidence: 99%
“…Pigs have also shown preference for umami flavors, including monosodium-glutamate (MSG) and similar chemicals, guanosine-5′-monophosphate and inosine-5′-monophosphate Hellekant and Danilova 1999). It has also been suggested that adding cheesy, fruity, meaty, and sweet flavors to foodstuffs may increase consumption and palatability by young pigs (McLaughlin et al 1983;Roura et al 2011).…”
Section: Physiological Senses Driving Motivationmentioning
confidence: 99%